Profiling Bartonella infection and its associated risk factors in shelter cats in Malaysia - Alias, Nurul Najwa Ainaa; Omar, Sharina; Ahmad, Nur Indah; Watanabe, Malaika; Sun, Tee Tay; Aziz, Nor Azlina; Mustaffa-Kamal, Farina (Korean Society of Veterinary Science, 2023)
Background: Poor disease management and irregular vector control could predispose sheltered animals to disease such as feline Bartonella infection, a vector-borne zoonotic disease primarily caused by Bartonella henselae (B. henselae). Objectives: This study investigated the status of Bartonella infection in cats from eight (n = 8) shelters by molecular and serological approaches, profiling the CD4:CD8 ratio and the risk factors associated with Bartonella infection in shelter cats. Methods: Bartonella eoxyribonucleic acid (DNA) was detected through polymerase chain reaction (PCR) targeting 16S-23S rRNA ITS gene, followed by DNA sequencing. Bartonella IgM and IgG antibody titre, CD4 and CD8 profiles were detected using indirect immunofluorescence assay (IFA) and flow cytometric analysis, respectively. Results: B. henselae was detected through PCR and sequencing in 1.0 (1/101) oral swab and 2.0 (1/50) cat fleas, while another 3/50 cat fleas carried B. clarridgeiae. Only 18/101 cats were seronegative against B. henselae, whereas 30.7 (31/101) cats were positive for both IgM and IgG, 8 (18/101) cats had IgM, and 33.7 (34/101) cats had IgG antibody only. None of the eight shelters sampled had Bartonella antibody-free cats. Although abnormal CD4:CD8 ratio was observed in 48/83 seropositive cats, flea infestation was the only significant risk factor observed in this study. Conclusion: The present study provides the first comparison on the Bartonella spp. antigen, antibody status and CD4:CD8 ratio among shelter cats. The high B. henselae seropositivity among shelter cats presumably due to significant flea infestation triggers an alarm of whether the infection could go undetectable and its potential transmission to humans.